Sistem Informasi Lelang Pengadaan Barang Online Menggunakan Metode Analytical Hierarchy Process (AHP) Pada PTAsia Pacific Fibers - Apit Priatna; Arif Maulana Yusuf; Yunus Gloria Liem (Journal of Applied Informatics and Computing, 2021)
The online auction system in the procurement of goods can make it easier to supervise and avoid fraud in the auction process, thereby creating transparency and accountability of data in the auction process to auction participants. The method used for data processing using AHP (Analytic Hierarchy Process). The stages in the AHP method begin with the process of defining the problem, creating a hierarchical structure that begins with a general purpose, followed by criteria and choice alternatives, Creating a paired comparison matrix, normalizing data, calculating the eigenvector value and testing its consistency, calculating the eigenvector of each Pairwise comparison matrix, Test the consistency of the hierarchy. If it does not comply with CR <0.100 then the assessment must be repeated. Calculations using the AHP (Analytic Hierarchy Process) method are faster than manual calculations so they can be more efficient and the level of data accuracy is close to perfect.